(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This work is devoted to the analysis of the role of motivation in the psychological development of unorganized youth and the main mechanisms of their labor orientation. The study thoroughly examined the motivational characteristics of young people, their interests, needs, personal values, as well as internal and external motivation factors. In the process of motivation, psychological barriers and ways to overcome them, adaptation strategies, the formation of personal identity, the influence of the social environment and family are of great importance. Also, in the vocational guidance of unorganized youth, ways have been developed to develop self-awareness and a positive attitude towards activity through psychological trainings, consultations, an incentive system, and effective means of communication.